Pengaruh Coloading Terhadap Perubahan Kenaikan Tekanan Darah Pada Pasien Spinal Anestesi - Pranandaru, Aditya; Sebayang, Septian Mixrova; Yudono, Danang Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Spinal anesthesia is a technique of administering local anesthetic drugs into the subarachnoid space. Spinal anesthesia is often used because it has several advantages, but can cause complications such as hypotension. One method to reduce the occurrence of hypotension is by administering coloading fluid. This study aims to determine the effect of coloading on changes and the time of increase in blood pressure in spinal anesthesia patients, this study is an experimental study with a pre-experimental research design with a pretest-posttest design approach. This study used quantitative methods, and obtained a sample of 58 samples. The results of the analysis using the willcoxon test showed that there was an effect of coloading on changes and time of increase in blood pressure in spinal anesthesia patients with a p value of 0.000 (<0.05). Coloading is effective in reducing the incidence of hypotension in spinal anesthesia patients.